Another Second Chance: Rehabilitation of marital rape offender for the victim’s recovery - Kasuma, Iva; Azhara, Farisa; Ilfa, Afida; Farhana, Shofiyah Adila (UI Scholars Hub, 2022)
Not all victims of marital rape want a divorce, generally victims long to maintain their marriage and for the perpetrators to correct their own behaviors. Victims are also bound to the strong culture that condones sexual relations without consent as long as it is carried out within the framework of a legal marriage. This study aims to demonstrate the importance of rehabilitation for offenders of marital rape by examining various laws and regulations in Indonesia and the obstacles to their implementation. Methodologically, data were obtained from doctrinal studies of Indonesian law and court decisions related to marital rape and empirical studies from a number of law enforcement officers as well as paralegals. The results show that the absence of a specialized law that regulates the rehabilitation of marital rape perpetrators impacts poorly on judges' decisions in domestic violence cases. There has been no court decision sentencing mandatory counseling as part of their rulings. Judges frequently view sexual violence within a limited scope of physical evidence; as a result, perpetrators are granted low sentences. Indonesia needs a specialized law that regulates the rehabilitation of marital rape perpetrators.